Students Opinion Towards the Implementation of Tophonetics Application in Learning Pronunciation - Hidayat, Khafid Wahyu; Aryanika, Septa; Muhassin, Moh.; Yanuar Fidaus, Wihda (Attractive : Innovative Education Journal, 2024)
The article was to development the students' opinion on the implementation of ToPhonetics application in learning pronunciation. The researchers conducted a survey model according to Masri. This technique learns data analysis techniques with descriptive analysis. Used to analyze data results from calculation questionnaires as well as results from interviews conducted. So that the data used in the study are grouped into two, namely qualitative data and quantitative data. And then analyzed descriptively to determine the fit between students' opinions when implementing the ToPhonetics application in learning pronunciation. The survey method is applied to describe the phenomenon of ToPhonetics application as a media for learning pronunciation. The subject of the research was the first semester students of English Education in the academic 2023/2024. The research sample which consisted of 28 students. The results of the students’ opinion on the implementation of the ToPhonetics application in pronunciation learning are positive opinions. The percentage reached 83.7% in the final result. Data shows that students love and enjoy the ToPhonetics application to learn pronunciation in English because of the features, usability, content, context, connectivity and mobilty in the ToPhonetics application. Based on the findings, it can be concluded that students have a positive opinion about the use of the ToPhonetics application to help them in improving pronunciation in learning English. Keywords: Tophonetics Application, Learning Pronunciation, Pronunciation